A web-based geotagged photo inventory for land use and land cover mapping of the East Kolkata Wetlands - Ghosh, Surajit; Dawn, A.; Soumya, B. (Zenodo, 2026)
The web-based inventory of geotagged photographs documenting the land use and land cover (LULC) characteristics of the East Kolkata Wetlands (EKW), a critical ecological and socio-economic landscape in eastern India. The platform, hosted at https://surajitghoshiwmi.github.io/EKW_S/ , integrates spatially referenced photographic observations with an intuitive web interface, enabling researchers, planners, and stakeholders to visually explore fine-scale LULC conditions across the wetland. The inventory compiles a systematically curated collection of geotagged images capturing diverse land cover types—such as water bodies, agricultural fields, built environments, settlement patterns, and vegetated areas—along with their precise geographic coordinates. Each entry provides contextual visual evidence that supports field validation, remote sensing interpretation, and temporal comparisons of landscape dynamics.